Pemanfaatan Teknologi Informasi Online Dalam Mendukung Pelayanan Paspor Di Kantor Imigrasi Kelas II TPI Kota Pare-Pare - Emilsyah Nur; Darsa Djaya Haedar (Program Studi Komunikasi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Mulawarman, 2021)
Improving the quality of technology is very important where every country tries to innovate in the field of technology to improve the image of its nation. Indonesia as a country with a very large human traffic always tries to create new innovations in all aspects in related fields, especially in the aspect of information technology in the field of Immigration. This research is a qualitative research using interview and observation data collection techniques. The results showed that the digital technology of the Class II TPI Pare-Pare City Immigration Office in providing passport application services has been evident and has fulfilled the need to serve the community. This is answered by physical evidence or tangible evidence that currently has met service standards. The reliability provided by the TPI Regional Immigration Office II Pare-Pare in the form of the website www.Pare-Pare.imigration.go.id is good enough, not just a formality as a government agency engaged in immigration, it is also strived for by the apparatus so that people use services Immigration services find it easy to interact with officials so that positive perceptions such as confidence in the services provided by the Class II TPI Class II Immigration Office officers in Pare-Pare City as service providers can grow in the eyes of the community.